Osteoporosis and venous thromboembolism: a retrospective cohort study in the UK General Practice Research Database. - Breart, G; Cooper, C; Meyer, O; Speirs, C; Deltour, N; Reginster, J (2010)
In a retrospective cohort study using the General Practice Research Database (GPRD), there was a greater association of venous thromboembolism (VTE) in osteoporotic than in non-osteoporotic female patients. No greater association was shown in treated patients with strontium ranelate or alendronate compared to untreated osteoporotic female patients.